Autolytic Activity and an Autolysis-Deficient Mutant of Clostridium acetobutylicum - Allcock, Errol R. (1981)
The optimum conditions for autolysis and autoplast formation in Clostridium acetobutylicum P262 have been defined. Autolysis was optimal at pH 6.3 in 0.04 M sodium phosphate buffer, and the bacterium produced latent and active forms of an autolytic enzyme. The ability of cells to autolyze decreased sharply when cultures entered the stationary phase. Autoplasts were induced by 0.25 to 0.5 M sucrose and were stable in media containing sucrose, CaCl(2), and MgCl(2). A pleiotropic autolysis-deficient mutant (lyt-1) was isolated. The mutant produced less autolysin than did the parent P262 strain, and it had an altered cell wall which was more resistant to both its own and P262 autolysins. The mutant formed long chains of cells, and lysozyme was required for the production of autoplasts. Growth of the P262 strain or the lyt-1 mutant was inhibited by the same concentrations of penicillin, ampicillin, and vancomycin. The lyt-1 mutant strain treated with the minimum growth-inhibitory concentration of penicillin autolyzed upon the addition of wild-type autolysin to the autolysis buffer at the same rate as did the untreated P262 strain. Chloramphenicol did not protect the penicillin-treated lyt-1 cells against autolysis enhanced by exogenous wild-type autolysin.